Research and Development Activity Matrix - New Conception in the Performance Evaluation of Research and Development - Molnár, László (Theory, Methodology, Practice – Review of Business and Management, 2011)
In the first part of the paper, we examine the different measurement methods of research and development activity within a corporation with particular attention to the composite indicators widespread in practice and to the multivariate statistical methods applied to create complex indices. In the second part, the research and development activity matrix is introduced in detail. The newly developed analysing method is a portfolio technique that describes the input and output activity of the research and development units in respect of quantity (performance) and quality (efficiency) and enables the categorisation of the observation units into four groups: stars, those lagging behind, quantity-oriented units and quality-oriented units.